Perancangan Media Belajar Bangun Datar berbasis Puzzle Digital dengan Mengintegrasikan Budaya Batik Lebak Banten - Primatama, Reza; Arisetyawan, Andika (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Understanding mathematical concepts is a basic thing that students need to master, so teachers must provide strong basic concepts so that students can understand mathematics completely. Based on the results of observations made in class II at the State Elementary School of Semanan 14 Petang, students still have difficulty understanding the material about flat shapes, especially in recognizing the shape of flat shapes. In addition, the evaluation media used is not culture-based. This became the basis for researchers to improve digital puzzle-based flat shape evaluation media by combining Lebak Banten batik culture. This research aims to create evaluation media based on the local wisdom of Lebak Banten to motivate students to study flat building material. The ethnographic method was used to collect information related to the Batik culture of Lebak Banten. Data collection techniques through interviews, observations and documentation studies. Furthermore, researchers use the ADDIE model to improve evaluation media at this level. The stages carried out were analysis, design, development, implementation, the researcher carried out media experiments in class II at the State Elementary School of Semanan 14 Petang and in the evaluation stage, the researcher reflected on the implications and corrections of the evaluation media. The results of this research are Lesson Plans and Two-Dimentional Figure evaluation media based on the Lebak Banten Batik Puzzle which are suitable for use.